Personality, fear of missing out and problematic internet use and their relationship to subjective well-being - Stead, Holly; Bibby, Peter A. (Elsevier, 2017)
The current research examines how an individual’s personality, their internet use and the extent to which they are inclined to fear ‘missing out’ impacts subjective well-being overall and in terms of emotional, physical, and personal relationship well-being. A total of 495 participants aged 18 to 30 (69% female) completed an online questionnaire via the Qualtrics website that included measures of the Big-5 personality dimensions (openness to experience, conscientiousness, extraversion, agreeableness, and emotional stability), fear of missing out, and problematic internet use. Participants were recruited through posting messages on the Facebook social media site linking to the Qualtrics website. Multiple linear regression and mediation analyses were conducted to examine the relationship between these factors and the measures of subjective well-being. With respect to overall subjective well-being, neither age nor sex were significant predictors. Conscientiousness, extraversion, emotional stability and agreeableness were positively related to overall subjective well-being. Importantly, both fear of missing out and problematic internet use made additional significant negative contributions to overall subjective well-being. Fear of missing out and problematic internet were both negatively correlated with emotional well-being and personal relationships well-being but not physical well-being. Overall, while personality directly impacts subjective well-being both fear of missing out and problematic internet negatively affect subjective well-being above and beyond personality.